2013
DOI: 10.1063/1.4822441
|View full text |Cite
|
Sign up to set email alerts
|

Scanning transmission electron microscopy investigations of self-forming diffusion barrier formation in Cu(Mn) alloys on SiO2

Abstract: Scanning transmission electron microscopy in high angle annular dark field mode has been used to undertake a characterisation study with sub-nanometric spatial resolution of the barrier formation process for a Cu(Mn) alloy (90%/10%) deposited on SiO2. Electron energy loss spectroscopy (EELS) measurements provide clear evidence for the expulsion of the alloying element to the dielectric interface as a function of thermal annealing where it chemically reacts with the SiO2. Analysis of the Mn L23 intensity ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…It is also observed that there is a shift in the diffraction peaks corresponding to ZSO towards higher angle in BTS4, suggesting a reduction in unit cell volume, as we discussed earlier in another study [37]. The reduction in the cell volume can be associated with the expulsion of the large Sm atom out of the ZnO's wurtzite structure or induced oxygen vacancy during the ERTA [44][45][46][47][48].…”
Section: Resultssupporting
confidence: 58%
“…It is also observed that there is a shift in the diffraction peaks corresponding to ZSO towards higher angle in BTS4, suggesting a reduction in unit cell volume, as we discussed earlier in another study [37]. The reduction in the cell volume can be associated with the expulsion of the large Sm atom out of the ZnO's wurtzite structure or induced oxygen vacancy during the ERTA [44][45][46][47][48].…”
Section: Resultssupporting
confidence: 58%
“…Discovering a suitable barrier to be inserted between a copper (Cu) layer and an Si substrate for certain microelectronic interconnects so as to reduce or prevent diffusion and reactions between the Cu and Si can be a formidable task as the dimensions of interconnects, and, hence, the barrier thickness, decrease to the nanometer range 1) as a result of the continuous trend of miniaturization in electronic devices. At the nanometer scale range, Cu resistivity increases owing to the electron and grain boundary scattering associated with the barrier layer.…”
Section: Introductionmentioning
confidence: 99%
“…Mn atoms segregate out easily of Cu-Mn alloys and react with SiO 2 to form a stable barrier layer. 6,22,23 Thermal stress conditions ranged from room temperature to 550 C. Figure 7 shows leakage current versus applied electric field curves of the (a) Cu-Al (4.6 at. %) alloy/SiO 2 /Si sample after 1 h of annealing at 300 C; (b) Cu-Al (4.6 at.…”
Section: A131-3 Parkmentioning
confidence: 99%
“…Self-forming barriers, when fabricated by directly depositing a Cu-M (Mn, Ti) alloy on dense SiO 2 substrate followed by heat treatment, have been demonstrated to function as effective Cu diffusion barriers. 6,7 The self-forming barrier approach requires just one Cu-M alloy layer instead of two (Ta/TaN barrier and Cu seed layer). The thinner overall film thickness helps to minimize the overhang when a PVD process is used and also reduces the aspect ratio, which is of benefit in the Cu plating process as it promotes void-free filling.…”
Section: Introductionmentioning
confidence: 99%